Prognosis of unexpected positive intraoperative cultures in arthroplasty revision: A large multicenter cohort. Issue 5 (November 2021) - Mancheño-Losa, Mikel; Lora-Tamayo, Jaime; Fernández-Sampedro, Marta; Rodríguez-Pardo, Dolors; Muñoz-Mahamud, Ernesto; Soldevila, Laura; Palou, Mariona; Barbero, José María; del Toro, María Dolores; Iribarren, José Antonio; Sobrino, Beatriz; Rico-Nieto, Alicia; et al.
Abstract: Background: The positive-intraoperative-cultures-type prosthetic joint infection (PIOC-PJI) is considered when surgical cultures yield microorganisms in presumed aseptic arthroplasty revisions. Herein we assess the risk factors for failure in the largest cohort of PIOC-PJI patients reported to date. Methods: A retrospective, observational, multicenter study was performed during 2007–2017. Surgeries leading to diagnose PIOC-PJI included only one-stage procedures with either complete or partial prosthesis revision. Failure was defined as recurrence caused by the same microorganism. Results: 203 cases were included (age 72 years, 52% females). Coagulase-negative staphylococci ( n = 125, 62%) was the main etiology, but some episodes were caused by virulent bacteria ( n = 51, 25%). Prosthesis complete and partial revision was performed in 93 (46%) and 110 (54%) cases, respectively. After a median of 3.4 years, failure occurred in 17 episodes (8.4%, 95%CI 5.3–13.1). Partial revision was an independent predictor of failure (HR 3.63; 95%CI 1.03–12.8), adjusted for gram-negative bacilli (GNB) infection (HR 2.68; 95%CI 0.91–7.89) and chronic renal impairment (HR 2.40; 95%CI 0.90–6.44). Treatment with biofilm-active antibiotics (rifampin/fluoroquinolones) had a favorable impact on infections caused by staphylococci and GNB. Conclusion: Overall prognosis of PIOC-PJI is good, but close follow-up is required in cases of partial revision and in infections caused by GNB. Highlights: The overall prognosis of unsuspected positive intraoperative cultures (PIOC) is good. Partial revision of the orthopedic device is the main risk factor for failure in PIOC. Gram-negative bacilli infection worsens the prognosis in PIOC. Biofilm-active antibiotics (rifampin and fluoroquinolones) may improve the prognosis. This is the largest cohort of patients with PIOC reported to date.